Multidimensional Fourier transforms on an amalgam type space - Liflyand, Elijah (Eurasian Mathematical Journal, 2019)
Generalizing the known results on the Fourier transforms on an amalgam type space, we introduce a multidimensional analogue of such a space, a subspace of L1(ℝn+). Integrability results for the Fourier transforms are obtained provided that certain derivatives of the transformed function are in that space. As an application, we obtain conditions for the integrability of multiple trigonometric series.